2010
DOI: 10.1159/000313588
|View full text |Cite
|
Sign up to set email alerts
|

Screening of Genital Anomalies in Newborns and Infants in Two Egyptian Governorates

Abstract: Background: External genital anomalies are among the most common congenital anomalies. Proper early diagnosis and management of genital abnormalities are of great importance to minimize medical, psychological and social complications. Aim: To detect the incidence of external genital anomalies and disorders of sex development (DSD) in Great Cairo and Qalyubiyah governorates. Subjects and Methods: 20,000 newborns and infants up to the age of 6 months coming for compulsory vaccination at primary health care units… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
16
0
5

Year Published

2011
2011
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 33 publications
1
16
0
5
Order By: Relevance
“…A 2-year-old 46,XY Tunisian girl with sexual ambiguity had the premature termination codon in exon 9, resulting in a lack of 105 amino acids of 281 the C-terminal region, a highly conserved region in different species [Ben Rhouma et al, 2012]. Finally, this report refers to the importance of genetic testing of HSD17B3 gene among Egyptian DSD patients and their families as a tool in the management of this relatively prevalent medical problem [Mazen et al, 2010].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…A 2-year-old 46,XY Tunisian girl with sexual ambiguity had the premature termination codon in exon 9, resulting in a lack of 105 amino acids of 281 the C-terminal region, a highly conserved region in different species [Ben Rhouma et al, 2012]. Finally, this report refers to the importance of genetic testing of HSD17B3 gene among Egyptian DSD patients and their families as a tool in the management of this relatively prevalent medical problem [Mazen et al, 2010].…”
Section: Discussionmentioning
confidence: 90%
“…The mutations were reported in a variety of ethnic groups including those in the Mediterranean region [George et al, 2010;Ben Rhouma et al, 2012;Neocleous et al, 2012]. On the other hand, despite the relative prevalence of DSD among Egyptian patients [Mazen et al, 2010], the literature lacks reports on molecular testing of HSD17B3 gene among them.…”
mentioning
confidence: 99%
“…Partial androgen insensitivity results in hypospadias and micropenis with gynecomastia' (PAIS, MIM# 312300). The prevalence of CAIS was estimated to be 1: 20,000-99,000 within genetic males [Oakes et al, 2008] and PAIS was reported to occur with similar frequency [Mazen et al, 2010].…”
mentioning
confidence: 99%
“…In Egypt, a study in Great Cairo and Qalyubiyah governorates showed a relatively high incidence of 93.5 per 10,000 cases with anomalies of the external genitalia [Mazen et al, 2010]. Hypospadias is a congenital hypoplasia of the penis, with displacement of the urethral opening along the ventral surface, often associated with a dorsal hooded foreskin and chordee [van der Zanden et al, 2010].…”
Section: Discussionmentioning
confidence: 99%